2005
DOI: 10.1210/jc.2005-0044
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Impact of Serum Calcitonin and Carcinoembryonic Antigen Doubling-Times in Patients with Medullary Thyroid Carcinoma

Abstract: Calcitonin DT may be superior to initial clinical staging and among the most powerful prognostic indicators in MTC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
205
1
9

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 352 publications
(220 citation statements)
references
References 27 publications
5
205
1
9
Order By: Relevance
“…In particular, the doubling time (Dt) of both Ct (Ct Dt) and CEA is a strong prognostic indicator for MTC recurrence and death (15,16,17,18).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the doubling time (Dt) of both Ct (Ct Dt) and CEA is a strong prognostic indicator for MTC recurrence and death (15,16,17,18).…”
Section: Introductionmentioning
confidence: 99%
“…156 In another nonrandomized and retrospective study, control patients were selected based on comparable serum calcitonin doubling time, a prognostic indicator of survival. 157 This study indicated that anti-CEA PRIT induced long-term disease stabilization in a significant number of patients, including 47% of high-risk patients. Furthermore, although there was no survival advantage in the entire study cohort, median survival was significantly longer in PRIT patients than control patients in the high-risk subgroup (110 versus 61 months; p < 0.03), 156 providing first evidence for the therapeutic efficacy of PRIT in metastatic, progressive solid tumors.…”
Section: Clinical Studies Of Hematologic Malignanciesmentioning
confidence: 72%
“…time (dt). We have shown that calcitonin dt is an independent predictor of survival, with a high predictive value, in patients with measurable serum calcitonin, even after repeated surgery 12 . at the end of that study, 41 patients with a calcitonin dt greater than 2 years were still alive 2.9 years to 29.5 years after their initial surgery.…”
Section: Selection Of High-risk Patients Who Need To Be Treatedmentioning
confidence: 74%
“…In a phase ii clinical trial, 31 patients with progressive metastatic mtc were injected with a median cumulative activity of 12.6 GBq, and response was defined as a decrease in serum calcitonin after therapy 21 . Interestingly, a post-therapeutic prolongation of calcitonin dt of at least 100% 12 was found in 58% of the patients, and a significantly longer survival was observed in responders than in non-responders. Unfortunately, drawing any valid conclusion with regard to a potential survival benefit is difficult because of a lack of pre-therapeutic selection of patients based on a validated prognostic factor such as calcitonin dt 12 .…”
Section: Alternative Treatment Modalitiesmentioning
confidence: 97%